"Point‐and‐Shoot" Synthesis of Metallic Ring Arrays and Surface‐Enhanced Optical Spectroscopy. Issue 10 (8th March 2018) - Rajeeva, Bharath Bangalore; Wu, Zilong; Briggs, Andrew; Acharya, Palash V.; Walker, S. Brett; Peng, Xiaolei; Bahadur, Vaibhav; Bank, Seth R.; Zheng, Yuebing
Abstract: The realization of optically active structures with direct‐write printing has been challenging, particularly in spatially constrained microfluidic devices which are essential for point‐of‐care (POC) applications. The existing techniques are limited by resolution, accessibility, and multistep fabrication constraints. "Point‐and‐shoot" strategies to achieve site‐specific fabrication of optically active Ag rings and on‐demand targeted surface‐enhanced optical spectroscopy are reported. Stable microbubbles over an Au nanoisland (AuNI) substrate are generated using a continuous‐wave laser at low power (≈0.5 mW µm −2 ). Analytical modeling of bubble generation process substantiates the evolution of ring morphology and its power dependence. The tunable Ag rings exhibit surface plasmon resonances in the mid‐IR regime from 3.8 to 4.6 µm, while the AuNI shows visible region response. The Ag ring over the AuNI imparts intensified surface‐enhanced Raman spectroscopy (SERS) activity owing to amplified hot spots at Ag ring/AuNI interface. As an example, SERS and surface‐enhanced infrared spectroscopy of rhodamine 6G, crystal violet, and 2, 4, 6‐trinitrotoluene molecules, respectively, are demonstrated. The applicability of this technique to perform in situ fabrication and SERS sensing in microfluidic channels is shown. Using a simple in situ approach toward optically active structures, our technique can synergize multiple surface‐enhanced optical spectroscopies to facilitate POC applications. Abstract : "Point‐and‐shoot" strategies are described to achieve site‐specific fabrication of optically active Ag rings and on‐demand targeted surface‐enhanced optical spectroscopy. Tunable Ag rings over an Au nanoisland substrate are fabricated to impart surface enhanced infrared sensing and surface enhanced Raman spectroscopy (SERS) capabilities. Further, in situ fabrication and SERS sensing in microfluidic channels with spatial constraints are also demonstrated.